Kinaesthetic Narrativization of Place in 360° Stereoscopic Flânerie (ENTHYMEMA, 2025)
In narrative film, space predominates over time, while in stereoscopic spherical cinema (3DSC), the transitions between spatial frames redefine the supremacy of space through orientational gaze and kinaesthetic flânerie by a deputy actant who explores the geopsychic space through the cartographic processes of narrativization. On one level, narrativization occurs through routes and geospatial cognitive mapping as well as horizontal cinescape projections within spatial frames. On the other level, it transpires at the intersection of a first-person perspective and platial experientiality, as the viewer’s body relocates, finding its place based on cultural, political, and social proximities. Thus, the coordinate system of 3DSC, inherently platial, is anchored in narrative pauses, devoid of temporal aspects except for the perpetual “now”. Whether 3DSC obliterates time through kinaesthetic wandering depends on the metalepsis of each narrative, the oscillating nature of the audience's perspectives, shifting between exocentric and egocentric views, ocularization and locus, auricularization and situatedness.